PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN WORD OF MOUTH MAHASISWA PROGRAM STUDI DIPLOMA III ADMINISTRASI PERPAJAKAN FISIP USU - Aida W Batubara; Paham - Ginting; Arlina Nurbaity Lubis (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The objective of the research was to know and to analyze the influence of servicequality on students’ word of mouth through their satisfaction in the Diploma III ofTaxation Administration Study Program, FISIP USU. The type of the researchwas descriptive quantitative and its nature was descriptive explanatory. Theresult of the research showed that 1) service quality had positive and significantinfluence on students’ word of mouth through their satisfaction, 2) satisfactionhad positive and significant influence on students’ word of mouth, and 3) therewas indirect influence of service quality on students’ word of mouth through theirsatisfaction with the value of 0.235, while there was direct influence of servicequality on students’ word of mouth with the value of 0.394 which indicated thatdirect influence was more dominant that indirect influence.